Frontal Sinus Trephination and Repeated Irrigation in a Cat with Chronic Rhinosinusitis: A Case Report - Hyomi Jang; Hyojun Kwon; Sunyoung Kim; Jiheui Sohn; Jong-in Kim; Dong-In Jung (Animals)
A 2-year-old neutered female domestic shorthair cat presented with chronic, progressively worsening upper respiratory symptoms that were unresponsive to long-term medical treatment. Initial management involved antibiotics, antivirals, and anti-inflammatory drugs, all of which failed to provide substantial clinical improvement. Diagnostic imaging with computed tomography revealed bilateral nasal and frontal sinus obstructions with viscous inflammatory exudate and localized osteolytic changes in the patient. Despite adjustments to the antimicrobial therapy regimen based on the PCR results, clinical signs persisted. Surgical intervention through frontal sinus trephination, physical removal of the exudate, placement of a temporary drainage tube, and repeated irrigation successfully resolved most of the clinical symptoms. Follow-up over two years showed sustained clinical improvement, with only mild intermittent serous nasal discharge reported. This case highlights the efficacy of surgical management, specifically frontal sinus trephination and repeated irrigation, in the treatment of cats with refractory chronic rhinosinusitis.